The Synchronization of GDP Growth in the G7 during U.S. Recessions. Is this Time Different? - Nikolaos Antonakakis; Johann Scharler (Johannes Kepler University of Linz, Department of Economics, 2010)
Using the dynamic conditional correlation (DCC) model due to Engle (2002), we estimate time varying correlations of quarterly real GDP growth among the G7 countries. In general, we find that rathe heterogeneous patterns of international synchronization exist during U.S. recessions. During the 2007 - 2009 recession, however, international co-movement increased substantially.
Keywords: E3; E32; F4; F41; 330; Dynamic conditional correlation; Business cycle synchronization; Recession; Konjunkturzusammenhang; Sozialprodukt; Vergleich; G-7-Staaten